2017
DOI: 10.1111/ctr.13001
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of portal vein thrombosis in patients with autoimmune hepatitis on the liver transplantation waiting list

Abstract: Liver transplantation (LT) is indicated in autoimmune hepatitis (AIH) for both acute presentation with liver failure and end-stage chronic liver disease. Few studies have suggested an association between AIH and coagulation disorders and a higher incidence of portal vein thrombosis (PVT) in patients with AIH listed for LT. The aim of this study was to determine the incidence of thrombotic complications, particularly PVT, in a cohort of 37 patients undergoing LT because of AIH. PVT was present before transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
(29 reference statements)
0
1
2
Order By: Relevance
“…There has been only a handful of studies investigating the crosstalk between biliary cirrhosis and PVT/portal spongiform. One study [ 30 ] reported an increased risk of PVT in the patients with autoimmune hepatitis awaiting liver transplantation, which is inconsistent with the findings of the present study. Regarding the underlying etiologies, the low risk of PVT and/or cavernous changes in the patients with biliary cirrhosis has been linked to the medications taken by this group of patients.…”
Section: Discussioncontrasting
confidence: 99%
“…There has been only a handful of studies investigating the crosstalk between biliary cirrhosis and PVT/portal spongiform. One study [ 30 ] reported an increased risk of PVT in the patients with autoimmune hepatitis awaiting liver transplantation, which is inconsistent with the findings of the present study. Regarding the underlying etiologies, the low risk of PVT and/or cavernous changes in the patients with biliary cirrhosis has been linked to the medications taken by this group of patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Other factors previously suggested as potential risk factors for PVT such as obesity, 45 large esophageal varices, previous variceal endoscopic treatment 8,13,14 or etiology of liver disease, especially metabolic dysfunction-associated fatty liver disease (MAFLD) 8,13,46,47 were not confirmed in our prospective study. However, only 13 patients in our cohort had MAFLD, so no firm conclusions can be drawn.…”
Section: Discussioncontrasting
confidence: 73%
“…Whereas another study shows that MASH patients have a lower risk of venous thromboembolism (VTE) [20]. Similarly, an observational study from Europe showed that among transplant-listed patients, PVT frequency was higher in nonmetabolic dysfunction-associated steatotic liver disease (MASLD) etiologies (autoimmune liver disease followed, cryptogenic, alcohol liver disease and viral liver disease) [21]. One European study had shown that chronic hepatitis C infection even without cirrhosis was associated with a higher pro-coagulant balance [22].…”
Section: Introductionmentioning
confidence: 99%